KONSELING DENGAN TEKNIK DEMONSTRASI UNTUK MENINGKATKAN KEMAMPUAN TOILET TRAINING PADA ANAK - Andri Kusuma Wijaya; Fatsiwi Nunik Andari; Wenti Dewentri (Universitas Bengkulu, 2022)
oilet training is a form of business carried out with the aim of controlling defecation (chapters) and urination (tub) which is carried out on children, this activity is carried out with the hope that children are able to prevent conditions from controlling chapters and tubs. Children need to get attention since especially in their growth and development which is carried out at the beginning of child development. So that it will produce children with abilities and qualities with great categories so that the future of children with superior categories will be achieved so as to produce healthy and intelligent children. The purpose of this study is to know the effect of counseling demonstration techniques to improve toilet training abilities in children. This research was conducted with a quantitative type of research where the design used can be found with a pre-experimental design using the One Group Pre-Test and Post-Test approaches. The univariate results of this study obtained the characteristics of 15 respondents, most of the respondents, namely 11 respondents (73.3%) were at the age of 5 years. For the results of the bivariate analysis using the Wilcoxon Signed Ranks Test statistical test, the p value (value) = 0.001 <0.05, so it can be concluded that there is an effect of counseling with demonstration techniques to improve toilet training abilities in children.